Hand and wrist orthoses for adults with rheumatological conditions: Practice guideline for occupational therapists - Therapists, C; Adams, J; Ball, C; Blenkiron, L; Bradley, S; McAlarey, K; Ramsey, L; Squire, R (College of Occupational Therapists, 2015)
This publication provides specific evidence-based recommendations which describe the most appropriate care or action to be taken by occupational therapists working with adults who may benefit from a hand or wrist orthosis as an intervention for a rheumatological condition. Physiotherapists, hand therapists, orthotists and others who prescribe or use othoses may also wish to refer to the guideline to inform their practice.